The Existence of Local Kings in Modern Democracy: Political Support in the Presidential and Vice Presidential Elections in East Nusa Tenggara in 2024 - Akhmad Syafruddin; Esrah Disyon Nino Am Benu; Boli Tonda Baso; Yohanes Fisher Keon (Journal of Social Science, 2025)
This paper will explain how the existence of local kings on the island of Timor in modern democracy is related to the strength, power and influence of the king in determining the direction of victory for one of the presidential and vice presidential candidates in the 2024 general election. The analysis will use Steven Lukes's theory of the face of power in looking at the power of kings who do not have formal power and cannot make decisions in the formal realm but have influence and power over the base or the people who mostly live in rural areas. The research method used is a Case Study with a qualitative approach with the aim of being able to more specifically find the impact or influence of local kings in the electability of the candidates competing in 2024. The results of the research show that the existence of local kings on the island of Timor in the presidential and vice presidential elections, especially for modern democracy, does not show the existence and has a significant impact on the security of the candidates. The power and existence of local kings are limited to customary institutions that have a role in socio-cultural life (marriage, death, thanksgiving for crops) and in the realm of local politics, customary institutions do not have the power to influence the political attitudes of the people in modern democracies such as elections. The political choices of the community are not determined by the influence of local kings, but the figure factors and work programs that have been carried out so far have become the consideration of the people in determining political choices. The local king is only a symbol of the power of the past which is now irrelevant to modern democracy in East Nusa Tenggara